Corticosteroid Pulses for Hospitalized Patients with COVID-19: Effects on Mortality - Ivan Cusacovich; Álvaro Aparisi; Miguel Marcos; Cristina Ybarra-Falcón; Carolina Iglesias-Echevarria; Maria Lopez-Veloso; Julio Barraza-Vengoechea; Carlos Dueñas; Santiago Antonio Juarros Martínez; Beatriz Rodríguez-Alonso; José-Ángel Martín-Oterino; Miguel Montero-Baladia; et al. (Mediators of Inflammation)
Objectives. To assess the influence of corticosteroid pulses on 60-day mortality in hospitalized patients with severe COVID-19. Methods. We designed a multicenter retrospective cohort study in three teaching hospitals of Castilla y León, Spain (865,096 people). We selected patients with confirmed COVID-19 and lung involvement with a pO2/FiO2<300, excluding those exposed to immunosuppressors before or during hospitalization, patients terminally ill at admission, or those who died in the first 24 hours. We performed a propensity score matching (PSM) adjusting covariates that modify the probability of being treated. Then, we used a Cox regression model in the PSM group to consider factors affecting mortality. Results. From 2933 patients, 257 fulfilled the inclusion and exclusion criteria. 124 patients were on corticosteroid pulses (250 mg of methylprednisolone for three days), and 133 were not. 30.3% (37/122) of patients died in the corticosteroid pulse group and 42.9% (57/133) in the nonexposed cohort. These differences (12.6%, 95% CI [8·54-16.65]) were statically significant (log-rank 4.72, p=0,03). We performed PSM using the exact method. Mortality differences remained in the PSM group (log-rank 5.31, p=0.021) and were still significant after a Cox regression model (HR for corticosteroid pulses 0.561; p=0.039). Conclusions. This study provides evidence about treatment with corticosteroid pulses in severe COVID-19 that might significantly reduce mortality. Strict inclusion and exclusion criteria with that selection process set a reliable frame to compare mortality in both the exposed and nonexposed groups.